2017
DOI: 10.1007/s00248-017-0943-9
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Microbial Diversity of Three Deep-Sea Hydrothermal Vents Southwest of the Azores

Abstract: Menez Gwen, Lucky Strike and Rainbow are the three most visited and well-known deep-sea hydrothermal vent fields in the Azores region, located in the Mid-Atlantic Ridge. Their distinct geological and ecological features allow them to support a diversity of vent communities, which are largely dependent on Bacteria and Archaea capable of anaerobic or microaerophilic metabolism. These communities play important ecological roles through chemoautotrophy, feeding and in establishing symbiotic associations. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 96 publications
2
21
0
Order By: Relevance
“…This result indicated that no strong environmental gradient drove the turnover of microbial communities in our sampling area. It is realized that temperature (Meyer et al 2013;Nunoura et al 2010), organic concentration (Mahmoudi et al 2015), metal composition (Cerqueira et al 2017) and reduction potential (Edlund et al 2008) are the common environmental factors driving community change in hydrothermal sediments. Considering the low density of hydrothermal vents and weak hydrothermal activities caused by the ultraslow spreading rate of SWIR, it is not surprising that the plume or fluids from distant active vents (about 40 km) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This result indicated that no strong environmental gradient drove the turnover of microbial communities in our sampling area. It is realized that temperature (Meyer et al 2013;Nunoura et al 2010), organic concentration (Mahmoudi et al 2015), metal composition (Cerqueira et al 2017) and reduction potential (Edlund et al 2008) are the common environmental factors driving community change in hydrothermal sediments. Considering the low density of hydrothermal vents and weak hydrothermal activities caused by the ultraslow spreading rate of SWIR, it is not surprising that the plume or fluids from distant active vents (about 40 km) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To compare the community composition of Tianzuo field with other hydrothermal vent fields, we downloaded the sequencing data of biofilms or sediments in six hydrothermal vents located at Mid-Atlantic Ridge (Cerqueira et al 2017), Arctic Mid-Ocean Ridge (Dahle et al 2015) and west SWIR ). The quality filter was processed following similar methods for our samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing evidence now support the role of gills as a bone fide immune-responsive tissue in B. azoricus, consistent with a suitable study model for exploring molecular interactions involving host-endosymbiont-mediated immune recognition events and adaptation mechanisms to deep-sea hydrothermal vent environments. Such adaptation mechanisms are likely to be influenced by the microbial community composition surrounding the mussel beds at hydrothermal vents and therefore it is important to continue metatranscriptomic and metagenomic studies [79] from the gill-associated microbial diversity and surrounding hydrothermal vent sediments [80,81] in view of the broader ecological organization and evolutionary importance of animal-bacterial microbiomes in chemosynthetic-based ecosystems in the deep sea [82,83].…”
Section: Discussionmentioning
confidence: 99%